Android-Based Physics Learning Media Integrated Landslide Disaster - Labibah, Ulfaturrona Nur; Wilujeng, Insih; Sulaiman, Syazana; Rahmawati, Lia (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
The purpose of a learning media is to become a learning device to facilitate the teaching and learning process in class. The learning process would be more efficient, and it would help students concentrate better. This research aims to develop an android-based learning media application so teachers and students can use it in the teaching and learning process. This research uses the R&D (Research and Development) method. This research uses ADDIE (Analysis, Design, Development, Implementation, and Evaluating) development model which results in a product, which is a valid learning media that can be implemented according to validator assessment that was done in the product trial test in Universitas Negeri Yogyakarta. It can be concluded that this media belongs in the good category based on assessment from media and material specialists validator, 85,7% average percentage is obtained and belongs to the valid category, so android-based physics media integrated with landslide disaster education is feasible to be used in physics learning. This media is made with an interesting and interactive interface so students can have a better understanding of physics learning integrated with landslide disaster education as well as disaster preparedness.